Comparative Study of Different Alternative Fuel Options for Shipowners Based on Carbon Intensity Index Model Under the Background of Green Shipping Development - Jin Zhang; Zhonghao Zhang; Ding Liu (Journal of Marine Science and Engineering)
The International Maritime Organization (IMO)’s annual operational carbon intensity index (CII) rating requires that from 1 January 2023, all applicable ships meet both technical and operational energy efficiency requirements. In this paper, we conduct a comparative study of different alternative fuel options based on a CII model from the perspective of shipowners. The advantages and disadvantages of alternative fuel options, such as liquefied natural gas (LNG), methanol, ammonia, and hydrogen, are presented. A numerical example using data from three China Ocean Shipping (Group) shipping lines is analyzed. It was found that the overall attained CII of different ship types showed a decreasing trend with the increase of the ship’s deadweight tonnage. A larger ship size choice can obtain better carbon emission reduction for the carbon emission reduction investment program using alternative fuels. The recommended options of using LNG fuel and zero-carbon fuel (ammonia and hydrogen) on Route 1 and Route 3 during the study period were analyzed for the shipowners. Carbon reduction scenarios using low-carbon fuels (LNG and methanol) and zero-carbon fuels (ammonia and hydrogen) on Route 2 are in line with IMO requirements for CII.